Room temperature fluorescence spectroscopy of benzo[a]pyrene metabolites on octadecyl extraction membranes - Alfarhani, Bassam (2016)
Benzo[a]pyrene (B[a]P) is a prototypic carcinogenic polycyclic aromatic hydrocarbon (PAH), which requires metabolic activation to produce its detrimental effects. Measurement of B[a]P metabolites in human urine could provide a direct way to assess individual differences in susceptibility to PAH-related cancer. This article focuses on the development of screening methodology for the routine analysis of B[a]P metabolites in urine samples. It explores the solid-surface room-temperature fluorescence (RTF) properties of 3-hydroxybenzo[ a]pyrene, benzo[a]pyrene-trans-9,10-dihydrodiol, benzo[a]pyrene-r-7,t-8,c-9-tetrahydrotriol and benzo[a]pyrene-r-7,t-8,c-9,c-10-tetrahydrotetrol previously extracted from urine samples with octadecyl-silica membranes. Relative standard deviations varying from 2.1% (benzo[a]pyrene-r-7,t-8,c-9-tetrahydrotriol) to 8.6% (3-hydroxy-benzo[a]pyrene) are obtained with the aid of fiber optic probe that eliminates the need for manual optimization of signal intensities. Analytical recoveries from human urine samples varied from 87.5 ± 3.1% (3-hydroxy-benzo[a]pyrene) to 99.8± 2.5% (benzo[a]pyrene-r-7,t-8,c-9,c-10-tetrahydrotetrol). The excellent analytical figures of merit and the simplicity of the experimental procedure demonstrate the potential of this approach for screening biomarkers of PAH exposure in numerous urine samples.